Experimental Studies on the Effects of Fine Particulate Matter (PM2.5) and Ozone on Plants - Yamaguchi, Masahiro (Journal of Japan Society for Atmospheric Environment / Taiki Kankyo Gakkaishi, 2021)
Plants support the lives of heterotrophs such as oxygen-consuming organisms including human beings. However, the atmospheric environment of plants has been changing, and probably getting worse, due to our industrial activity. Many researchers have indicated the adverse effects of air pollutants on plants based on their many studies on the effects of SO2, NO2, acid deposition, such as acid rain, particulate matter, and photochemical oxidants, such as tropospheric ozone (O3), on plants. To expand the knowledge and develop the discussion on the effects of air pollutants on plants, I have conducted experimental studies regarding the effects of fine particulate matter (PM2.5) and O3 on plants. In the present paper, I have summarized the results obtained from the experimental studies on the long-term effects of black carbon (BC) and ammonium sulfate (AMS) particles on plants, and those on the evaluation of O3 effects on plants based on the cumulative stomatal O3 uptake. Moreover, I introduced the experiments conducted in Nagasaki, Japan, where the transboundary air pollution has been frequently observed, in order to evaluate effects of the long-range transported air pollutants such as PM2.5 and O3 on plants.